2021
DOI: 10.3390/agronomy11101923
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Coherent Laser Stimulation of Seeds and a Fungal Inoculum to Increase the Productivity and Health of Soybean Plants

Abstract: The laser stimulation of seeds is regarded as a modern method of seed enhancement. Our study evaluated the productivity and health of soybean plants resulting from the coherent irradiation of seeds and irradiation of an arbuscular mycorrhizal fungi (AMF) inoculum. The two-factor pot experiment took into account (1) the type of irradiated biological material (seeds, AMF inoculum, and seeds and inoculum) and (2) the means of irradiation (red laser—LR, blue laser—LB, red and blue laser—LR + LB, and control). Seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Yan et al [9] suggested that in the near future interdisciplinary research on bacterial communities associated with AMF (arbuscular mycorrhizal fungi) should be adopted as an integrated tool for identifying the best combinations of bacterial communities capable of increasing the efficiency of nutrient utilization and the resistance of crop plants and of enhancing nutraceutical compounds among species of crop plants. Dłu żniewska et al [10] presented interdisciplinary results of studies, which combined two different methods of biostimulation, i.e., biological stimulation through the application of a mycorrhizal inoculum and physical stimulation through the application of laser light to seeds. This method has unlimited potential due to the positive synergistic effect obtained when it is used in combination with other methods of seed biostimulation, such as biological methods [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yan et al [9] suggested that in the near future interdisciplinary research on bacterial communities associated with AMF (arbuscular mycorrhizal fungi) should be adopted as an integrated tool for identifying the best combinations of bacterial communities capable of increasing the efficiency of nutrient utilization and the resistance of crop plants and of enhancing nutraceutical compounds among species of crop plants. Dłu żniewska et al [10] presented interdisciplinary results of studies, which combined two different methods of biostimulation, i.e., biological stimulation through the application of a mycorrhizal inoculum and physical stimulation through the application of laser light to seeds. This method has unlimited potential due to the positive synergistic effect obtained when it is used in combination with other methods of seed biostimulation, such as biological methods [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Dłu żniewska et al [10] presented interdisciplinary results of studies, which combined two different methods of biostimulation, i.e., biological stimulation through the application of a mycorrhizal inoculum and physical stimulation through the application of laser light to seeds. This method has unlimited potential due to the positive synergistic effect obtained when it is used in combination with other methods of seed biostimulation, such as biological methods [10,11]. Dłu żniewska et al [10] showed that the health of young soybean plants was improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using artificial light sources is more useful than using chemicals to control the seed quality, flowering, yield, and diseases in the crops and simultaneously reduce the environmental impact. Consequently, the use of LED lights in agricultural farming has been increasingly noticed [ 2 , 3 , 4 , 5 ]. Several studies have shown that changes in LED wavelengths and light intensity could be the tools to manipulate plant growth, photosynthesis performance, and plant secondary metabolism pathways for the production of functionalized foods [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is using various physical methods such as E-ventus or biolaser seeds photostimulations (Tigges et al 2002, Dłużniewska et al 2021. Poppy seed treated with the E-ventus method is commercially offered in the Czech Republic.…”
mentioning
confidence: 99%